Koncepcje pomiaru wyników na potrzeby strategicznego zarządzania efektywnością przedsiębiorstw oraz efekty ich wdrażania - Skoczylas, Wanda (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The main results measurement systems in today's operational area are based on accounting, which is not enough for strategic management. This article proves that there is a need to create some new systems, and then implement them for steering. There are many systems corporate performance measurement systems. The implementation of these system causes efficiency growth in corporations. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1183, s. 447-457